2020
DOI: 10.1148/radiol.2020192437
|View full text |Cite
|
Sign up to set email alerts
|

Update to the Society of Radiologists in Ultrasound Liver Elastography Consensus Statement

Abstract: This multidisciplinary update of the Society of Radiologists in Ultrasound consensus statement on liver elastography incorporates the large volume of new information available in the literature since the initial publication. The recommended procedure for acquiring stiffness measurements is reviewed. There has been substantial improvement in the acoustic radiation force impulse (ARFI) technology-most notably the addition of a quality assessment of the shear wave propagation. Due to the efforts of the Quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
295
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 278 publications
(353 citation statements)
references
References 79 publications
(86 reference statements)
8
295
0
5
Order By: Relevance
“…General anesthesia significantly increases LS measurements in healthy children (5.4 kPa vs. 4.2 kPa; p < 0.01) 16 . For those systems that allow real‐time 2D‐SWE, a cine clip of multiple shear wave images can be obtained and then reviewed to locate areas with little motion and neutral breathing 21 …”
Section: Techniquesmentioning
confidence: 99%
“…General anesthesia significantly increases LS measurements in healthy children (5.4 kPa vs. 4.2 kPa; p < 0.01) 16 . For those systems that allow real‐time 2D‐SWE, a cine clip of multiple shear wave images can be obtained and then reviewed to locate areas with little motion and neutral breathing 21 …”
Section: Techniquesmentioning
confidence: 99%
“…To ensure accurate measurement of the shear-wave speed with acoustic radiation force impulse, standardized acquisition parameters have been recently developed (29)(30)(31)(32). A patient, after fasting at least 4 hours, is positioned supine or slight (,30°) left lateral oblique, with the right arm in maximal abduction to increase the intercostal space for probe placement (Fig 4).…”
mentioning
confidence: 99%
“…Imaging in the setting of hepatic inflammation, elevated transaminase levels, and vascular congestion, among other factors, may overestimate liver stiffness (33). Correlation with serum transaminase levels and noting aspartate transferase level or alanine aminotransferase elevation more than five times the upper limit of normal, which may lead to the overestimation of liver fibrosis, is suggested (29). Some investigators have suggested using separate SWE thresholds based on transaminase levels; however, these thresholds are not broadly validated (29,33).…”
mentioning
confidence: 99%
See 2 more Smart Citations